Combined Strategy of Targeted Therapy and Immunotherapy for Bladder Cancer - Zonghua Wang (International Journal of Biology and Life Sciences, 2026)
Bladder cancer is a highly prevalent malignant tumor in the urinary system worldwide, and the treatment has been long facing significant challenges. Immunotherapy represented by PD-1 (programmed death receptor-1)/PD-L1 (programmed death ligand-1) inhibitors and targeted therapies such as antibody-drug conjugates have already changed the landscape. However, the efficacy of a single drug is limited, and the problem of drug resistance is quite prominent. The combined treatment strategy, through the deep synergy of pharmacology and immunology, aims to overcome tumor heterogeneity and immunosuppressive microenvironments. It has become a core research direction in the treatment of bladder cancer. This review systematically elaborates the synergistic biological mechanisms by which targeted drugs induce immunogenic cell death, re-adjust the tumor immune microenvironment, and immune checkpoint inhibitors amplify and prolong the therapeutic effect. It focuses on elaborating the groundbreaking clinical evidence achieved by the "ADC + immunotherapy" approach, such as ennozumab combined with pembrolizumab, in advanced first-line and neoadjuvant treatments, and also summarizes the emerging methods including dual immunotherapy combinations, immunotherapy combined with other regulators, and oncolytic viruses. Furthermore, this article thoroughly examines the challenges that may arise from combined treatment, such as the complexity of drug resistance mechanisms and the optimization of drug toxicity management. Finally, a series of prospects were presented regarding future directions such as the development of drugs targeting new targets in the tumor microenvironment. This article aims to provide an academic reference for a comprehensive understanding of the current status and future prospects of targeted and immunotherapy combined strategies for bladder cancer.